2012
DOI: 10.1002/cphc.201200510
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Charge Transfer and Charge Recombination by Insertion of a Naphthalene‐Based Bridge in Molecular Dyads Based on Borondipyrromethene (Bodipy)

Abstract: The photophysical properties of two related dyads based on a N,N-dimethylaniline donor coupled to a fully-alkylated boron dipyrromethene (Bodipy) acceptor are described. In one dyad, BD1, the donor unit is attached directly to the Bodipy group, whereas in the second dyad, BD2, a naphthalene spacer separates the two units. Cyclic voltammograms recorded for the two dyads in deoxygenated MeCN containing a background electrolyte are consistent with the reversible one-electron oxidation of the N,N-dimethylaniline g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 89 publications
1
20
0
Order By: Relevance
“…Decay of this species occurs with a time constant of approximately 1 ns to form a mixture of the triplet-excited state and the ground state but without clear population of a charge-separated species. Such behavior has been reported previously for Bodipyrelated exciplexes [43] in solvents of medium polarity, and intersystem crossing within exciplexes is well known. [44] The triplet-excited state can be seen after excitation of BOD-DCV with a 4 ns laser pulse at 470 nm (Figure 7), for which the decay profile is monoexponential with a lifetime of approximately 90 ms in the absence of dissolved oxygen.…”
Section: Laser Spectroscopysupporting
confidence: 82%
“…Decay of this species occurs with a time constant of approximately 1 ns to form a mixture of the triplet-excited state and the ground state but without clear population of a charge-separated species. Such behavior has been reported previously for Bodipyrelated exciplexes [43] in solvents of medium polarity, and intersystem crossing within exciplexes is well known. [44] The triplet-excited state can be seen after excitation of BOD-DCV with a 4 ns laser pulse at 470 nm (Figure 7), for which the decay profile is monoexponential with a lifetime of approximately 90 ms in the absence of dissolved oxygen.…”
Section: Laser Spectroscopysupporting
confidence: 82%
“…However, this hypothesis does not explain the high dependence on 1 O 2 production with the solvent polarity. An alternative explanation for the efficiency of the orthogonal BODIPY dimers as PSs for 1 O 2 production is the triplet‐state population taking place from ICT states generated by charge recombination (ICT transition) in the singlet excited state (16‐108). Nevertheless, the dependence of 1 O 2 generation of halogen‐free orthogonal BODIPY dimers on solvent polarity is in good agreement with a spin–orbit charge‐transfer intersystem crossing (SOCT‐ISC) mechanism (12,109), which basically operates in orthogonal donor–acceptor dyads.…”
Section: Resultsmentioning
confidence: 99%
“…During those studies, it was found that the bridging unit plays a key role in the transfer rates, in particular in the recombination to the ground state. Using a bodipy dye as donor and a simple amine as acceptor, charge transfer rates with or without a naphthalene bridging unit were measured; however, the energy levels of donor and acceptor did not display an optimal match and no direct effect could be observed [14]. It was found that a bridging unit with a strong coupling between donor and acceptor promotes a rapid recombination.…”
Section: Small Dyad Systemsmentioning
confidence: 98%